Drip fertigation for Enhancing crop and water productivity - Mohanty, S.; Sandal, S. K.; Rautaray, S. K.; Sarangi, A. (Indian Farming, 2025)
Drip fertigation is an effective and convenient mean of applying water and fertilizer. In this method, water soluble fertilizers are applied as per crop needs in the vicinity of plant roots using drip line and drippers. This method is useful in water scarce situations, and for horticultural and cash crops requiring high dose of nutrients and water at frequent intervals. Up to 90 % of the appliednutrients are absorbed with fertigation while it is only about 40% with the conventional surface application of dry fertilizer. It reduces fertilizer dose by about 25 % for most soils (loamy sand, sandy clay, clay loam and silty clay loam) and thereby, fertigation has potential to partially help in overcoming the fertilizers crisis. Adverse effects of chemical fertilizers on environment can also be reduced. Results from All India Coordinated Research project on Irrigation Water Management showed that there was 26–45% increase in crop yield due to drip fertigation. Water productivity in crops due to fertigation ranged from 30.2 to 103.2 kg/ha.mm. Results further indicated that 25% of recommended N, P and K fertilizer can be applied as basal dose at planting using conventionalsolid fertilizers. For P, even up to full dose can be placed as basal in certain soils. Location specific fertigation schedules should be followed for higher water, nutrient and economic efficiency.